LA RELACIÓN A FINALES DEL PERÍODO HORIZONTE TEMPRANO E INTERMEDIO TEMPRANO EN CONVENTOMOQO, VALLE DEL CUSCO - Delgado González, Carlos (2017)
This work treats about the interaction between the ceramic styles Derived Chanapata and the styles of the Early Intermediate Period like Qotakalli and a “local” ceramic during this period and the beginning of the Middle Horizon in the archaeological site Conventomoqo in the Huatanay valley. Conventomoqo is an interesting site where a stratigraphic sequence from the Early Horizon to the Inca period exists. The site was first identified by Bauer in his extensive prospection of the Cusco valley (2008) and by the Nacional Institute of Culture of Cusco. The archaeological excavations allowed us to obtain indications to propose that the Derived Chanapata style was still being produced and used in Conventomoqo when the Qotakalli style was densely diffused in the Huatanay valley. Furthermore the results of the excavation and the analysis of the ceramic led us to put a question mark on a ceramic style that we call “local” for the valley of Cusco and if it could be contemporary with Qotakalli.